In Ataxia-Telangiectasia, Oral Betamethasone Administration Ameliorates Lymphocytes Functionality through Modulation of the IL-7/IL-7Rα Axis Paralleling the Neurological Behavior: A Comparative Report of Two Cases. (17th February 2021) - Prencipe, Rosaria; Cirillo, Emilia; Giardino, Giuliana; Gallo, Vera; Menotta, Michele; Magnani, Mauro; Barone, Maria Vittoria; Palamaro, Loredana; Scalia, Giulia; Del Vecchio, Luigi; Pignata, Claudio
ABSTRACT: Ataxia-Telangiectasia (A-T) is characterized by cerebellar neurodegeneration and immunodeficiency. Recent studies suggest that very low glucocorticoids (GCs) doses may help improve A-T neurological phenotype in some patients. Interestingly, in GCs studies an unexpected improvement of lymphocytes proliferation in some A-T patients has been observed. GCs are able to upregulate IL-7 Rα expression and rescue it from the recycling. In this study, we compared several immunological functions, including PBMC proliferative responses, cell activation events and IL-7/IL-7 Rα axis functionality, with the neurological behavior during an in-vivo GCs treatment between the most Responder patient to GC and the Non-Responder at all. During in-vivo GC treatment, we observed an increase of lymphocyte proliferation upon stimulation with PHA or IL-7 only in the Responder. This finding paralleled the increase in the surface expression of IL-7 R and up-regulation of the CD69 T-cell activation marker. Internalization and recycling of IL-7 R occurred properly only in the Responder. Microarray analysis revealed a remarkable difference in the DE-genes levels among Responder and Non-Responder, mostly concerning miRNAs and Multiple Complex families. Our findings suggest that the improvement of lymphocyte functionality, which correlates to the neurological behavior, is mediated through an effect of GCs on the IL-7/IL-7 Rα axis.